Effectiveness of vitamin E as a treatment of primary dysmenorrhea in pubertal adolescents - Wagito Wagito; Siska Mayasari Lubis; Melda Deliana; Hakimi Hakimi (Paediatrica Indonesiana, 2011)
Background Primary dysmenorrhea is a common complaint among adolescents. Absenteeism from work and school are associated with the severity of symptoms. Vitamin E is an alternative treatment for primary dysmenorrhea.Objective To evaluate the effectiveness of vitamin E as a treatment of primary dysmenorrhea.Methods We conducted a randomized, double-blind, controlled trial from August to October 2009. We included female adolescents 'With primary dysmenorrhea in this study. Subjects were divided into 2 groups by simple randomization. Each group received either 200 units of vitamin E or a placebo twice daily, beginning two days before menstruation and continuing until the third day of menstruation. Treatment was repeated for three menstrual cycles. Subjects recorded the severity and duration of pain in a daily diary. Data was analyzed using Chiô€square, Mannô€W hitney Uô€test, and independent T-test.Results One hundredô€sixteen primary dysmenorrhea subjects enrolled in our study. By simple randomization, they were divided into two groups of 58 subjects each. There were no statistically significant differences between the two groups in the severity and duration of pain before the start of treatment and after 1 month of treatment. After treatment for 2 months and 3 months, there were statistically significant differences in pain severity (P=0.013, 95%CI -0.54 to -0.11; and P=0.0001, 95%CI -0.67 to -0.26, respectively) and pain duration (P=0.025, 95%CI -0.65 to -0.07 and P=0.007, 95%CI -0.75 to -0.12, respectively) between the 2 groups.Conclusion Vitamin E was effective in treatment of primary dysmenorrhea in pubertal adolescents after 2 and 3 months of treatment.